THE IMPACT OF DIGITAL TRANSFORMATION ON THE QUALITY OF PUBLIC SERVICES - Khayrullayev Javohir Sheraliyevich (The Conference Hub, 2025)
Digital technology is an integral part of modern life, and today the computer is a factor in all areas. The goal of technological technologies of public services is to create convenience for every citizen. Today, more than 760 electronic connections are being implemented in Uzbekistan on the single interactive public services portal "My.gov.uz". The population has access to the service quickly and in all regions. This is due to its control, supervision and control over the time associated with visiting public service bodies. The level of economic efficiency is much higher than in the traditional system, and technology is used to determine the delivery of public services and ensure openness.
Keywords: Digital transformation, public services, e-government, security systems, My.gov.uz, electronic services, digital identification, electronic signature, transparency, economic efficiency.